2021
DOI: 10.3390/antibiotics10050477
|View full text |Cite
|
Sign up to set email alerts
|

A Complementary Herbal Product for Controlling Giardiasis

Abstract: Giardiasis is an intestinal protozoal disease caused by Giardia lamblia. The disease became a global health issue due to development of resistance to commonly used drugs. Since many plant-derived products have been used to treat many parasitic infestations, we aimed to assess the therapeutic utility of Artemisia annua (A. annua) for giardiasis. We showed that NO production was significantly reduced whereas serum levels of IL-6, IFN-γ, and TNF-α were elevated in infected hamsters compared to uninfected ones. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…Recent studies have also shown the importance not only of CD4 + producing Th1 cytokines, IFNγ and TNFα, but also of CD4+ producing IL-17A cells (Th17) in acute giardiasis Saghaug et al 26 Our results are consistent with the findings of Abd-Elhamid et al, 58 who found increased levels of IL-6, IFNγ and TNFα with lowered NO production in hamsters infected with G. lamblia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recent studies have also shown the importance not only of CD4 + producing Th1 cytokines, IFNγ and TNFα, but also of CD4+ producing IL-17A cells (Th17) in acute giardiasis Saghaug et al 26 Our results are consistent with the findings of Abd-Elhamid et al, 58 who found increased levels of IL-6, IFNγ and TNFα with lowered NO production in hamsters infected with G. lamblia.…”
Section: Discussionsupporting
confidence: 91%
“…Giardia induced the same degree of proliferation and interferon γ production by CD4 + T‐lymphocytes in intestine and blood Weatherhead et al 23 Moraes et al 57 suggest that IFN‐γ plays a beneficial role for the host by activating neutrophils and MN cells to kill the parasite. Recent studies have also shown the importance not only of CD4 + producing Th1 cytokines, IFN‐γ and TNF‐α, but also of CD4+ producing IL‐17A cells (Th17) in acute giardiasis Saghaug et al 26 Our results are consistent with the findings of Abd‐Elhamid et al, 58 who found increased levels of IL‐6, IFN‐γ and TNF‐α with lowered NO production in hamsters infected with G. lamblia .…”
Section: Discussionsupporting
confidence: 91%
“…Group A represent uninfected mice (negative control) while Groups B, C, and D were starved for 12 h then orally infected, each with 300 T. spiralis larvae, using a syringe ( 24 ). Group B did not receive any treatment (infected untreated mice), whereas Group C and D infected mice were treated with 50 mg/kg albendazole ( 49 ) and 300 mg/kg of the A. annua ethanolic extract, respectively ( 18 , 33 ). All treatments started from the third day post-infection (3 dpi) for three consecutive days ( 18 , 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…Artemisia annua (A. annua) , a plant known for its malarial properties, has been researched for a variety of biological activities, including anticancer, antidiabetic, and antibacterial properties ( 25 32 ). In addition to treatment of several parasitic diseases such as giardiasis ( 33 ), toxoplasmosis ( 34 ) and leishmaniasis ( 35 ). A. annua contains a wide range of chemical compounds ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, the giardicidal effect of ginger was more pronounced than the effect of curcumin [ 127 ]. In vitro assessment also indicated a dose-dependent giardicidal effect of a chloroformic extract of Artemisia annua [ 128 , 129 ]. Olive leaf extracts and extracts of Satureja khuzestanica (a plant used for medical purposes by nomads in southwestern Iran) show in vitro giardicidal effects in the range of metronidazole or better [ 130 ].…”
Section: Treatment Attempts Alternative To the “5-nitroimidazoles Standard”mentioning
confidence: 99%